Perlindungan Nasabah Bank Terhadap Tindakan Phishing Studi Pada PT Bank Rakyat Indonesia (Persero) Tbk - Febbyanti Rahmadian; Muhammad Maksum; Mara Sutan Rambe (JOURNAL of LEGAL RESEARCH, 2020)
This study aims to determine the protection provided by PT Bank Rakyat Indonesia (Persero) Tbk, known as BRI Bank to its customers from phishing crimes. This research explains the basis of the bank's responsibility to protect its customers from phishing, various regulations regarding customer protection from phishing in Indonesia, and how the implementation of BRI Bank in protecting its customers from phishing, both preventively and repressively. This research method uses a statutory approach (statue approach) by using Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking and uses a conceptual approach which is used to determine the ideal form of protection against bank customers from phishing acts. This research proves that the protection of customers at Bank BRI from phishing can be realized if customers are aware of their rights and obligations, then BRI Bank is more active in providing education to its customers.Keywords: E-Banking, Phishing, Legal Protection